Argument pattern used by samina Ali's speech what does the quran really say about a muslim woman's hijab ? - Diva Hana Zhafirah Hardy (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2021)
wt,1/ yna, c.1